Construction of a heat-resistant strain of Lentinus edodes by fungal Hsp20 protein overexpression and genetic transformation - Ling, Yun-Yan; Ling, Zhi-Lin; Zhao, Rui-Lin (Frontiers in Microbiology, 2022)
The shiitake mushroom (Lentinus edodes) is the second most popular edible mushroom globally due to its rich nutritional value and health benefits associated with consumption. However, the characteristics of growing at low temperatures limit the area and time of its cultivating. We selected a low-temperature cultivar as the original strain. We proposed to construct a heat-shock protein expression vector to achieve genetic transformation in this low-temperature strain to improve the survivability of the strain against the heat-shock response. In this study, an overexpression vector pEHg-gdp-hsp20 for the heat shock protein 20 gene of A. bisporus was constructed using a homologous recombination method. This vector was transferred into dikaryotic and monokaryotic mycelia by the Agrobacterium tumefaciens-method. The integration of hygb and hsp20 into the genome of L. edodes mycelia was verified by growth experiments on resistant plates and PCR analysis. The expression of the reporter gene mgfp5 was verified by fluorescence microscopy analysis and statistically resulted in 18.52 and 26.39% positivity for dikaryon, and monokaryon, respectively. Real-time PCR analysis showed that the expression of the hsp20 gene was more than 10-fold up-regulated in the three transformants; the mycelia of the three overexpression transformants could resume growth after 24 h heat treatment at 40°C, but the mycelia of the starting strain L087 could not recover growth at 25°C indicating that strains that successfully expressed hsp20 had greater overall recovery after heat shock. According to the study, A. bisporus hsp20 gene overexpression effectively improves the defensive capability of low-temperature mushroom strains against heat shock, laying the foundation for breeding heat-resistant high-quality transgenic shiitake mushrooms.